The Theory of Discourse in Modern Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines the peculiarities of discourse and study of its various types. The analysis of various interpretations of discourse, its essence and content is given. The paper presents approaches to the definition of the concept of discourse: functional, formal, situational and cognitive. Within the framework of this study, discourse is understood as the unity of linguistic and cognitive structures in their interaction, since the linguistic sphere cannot function in isolation from the cognitive one, this interaction is a communication process.